Respuesta :

First, you would distribute the -4 to the x and 6 and the new equation would be 12-4x-24=2x+18. Because you want to combine like terms, the new equation after you added everything you could would be -4x-12=2x+18. Subtract 2x from both sides to get -6x-12=18. Add 12 to both sides to get -6x=30. Divide both sides by -6 to get x=-5. Hope this helped!
the answer to this problem is -5  and to do this you start by distributing the -4 to the x and the 6 which will leave you to this equation 12-4x+(-24)=2x=18
you then add the -4x to the 2x which will give you this equation 12+(-24)=6x+18 notice that whenever i do something on one side i do it to the other side also so then after you get that equation you take away the 12 from both sides which will leave you to this equation -24=6x+6 you then take away the 6 from both sides and that will equal to this -30=6x you then divide and that will give you the answer which is x=-5